High resolution C-isotopic data from microbialites in the aftermath of the end-Permian mass extinction in South China - Huang, Xiemin; Li, Dandan; Zhang, Xiaolin; Xu, Yilun; Sun, Lilin; Li, Menghan; Shen, Yanan (Frontiers in Earth Science, 2022)
Globally, Late Permian to Early Triassic carbonate rocks record several pronounced positive and negative C-isotope excursions, indicating a dramatic reorganization of the global carbon cycle. These C-isotopic anomalies provide important constraints on environmental changes that occurred during the end-Permian extinction and the subsequent delayed biotic recovery. In this study, we present high-resolution carbonate C-isotopic data (δ13Ccarb) spanning the Permian-Triassic transition at Dajiang, South China. Our results reveal a general decrease in δ13Ccarb of ~3.3‰ during the microbialite formation which was followed by an increase. C-isotopic chemostratigraphic correlation between the Dajiang section and the Global Boundary Stratotype Section and Point (GSSP) at Meishan suggest a hiatus of several thousands of years between the pre-extinction skeletal limestones and the microbialite deposition in the aftermath of the end-Permian extinction in South China. We suggest that multiple sources of 13C-depleted dissolved carbon are required to explain the negative δ13Ccarb excursions as well as the δ13Ccarb differences among microbialites deposited in various paleogeographic locations. Our study shows that carbon cycles during the formation of microbialite may have been more complex than previously thought, and cessation of microbialite formation may have been controlled by both global and local environmental changes.